2004
DOI: 10.2320/matertrans.45.3136
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Damage and Fracture of Forging Die by Fractal Property of Acoustic Emission

Abstract: The detection of damage to and fracture of cold forging tools during forming operation by fractal property of acoustic emission (AE) is performed. First, a tensile test on tool steel is conducted to elucidate the fractal dimensions of deformation-induced and fracture-induced AEs. The resultant fractal dimensions are 1.97 and 1.44. Next, the change in the fractal dimension of AE from a die insert is investigated under cold forward extrusions. Workpieces with a conversion coating film are used to eliminate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Virkar et al [29] found that the b value could be used to predict rock failure and analyze rock damage. Hayakawa et al [30] researched the AE fractal characteristic of cold forging tool damage during forming operation and calculated the AE fractal dimension of deformation and fracture, which verified that fractal dimension can be used to describe cold forging tool failure as an effective indicator. In summary, many domestic and foreign scholars have extensively investigated AE characteristics and precursor characteristics of rock failure.…”
Section: Introductionmentioning
confidence: 96%
“…Virkar et al [29] found that the b value could be used to predict rock failure and analyze rock damage. Hayakawa et al [30] researched the AE fractal characteristic of cold forging tool damage during forming operation and calculated the AE fractal dimension of deformation and fracture, which verified that fractal dimension can be used to describe cold forging tool failure as an effective indicator. In summary, many domestic and foreign scholars have extensively investigated AE characteristics and precursor characteristics of rock failure.…”
Section: Introductionmentioning
confidence: 96%
“…Żabiński et al (2014) used force sensors and binary sensors to detect three types of defects in the cold forming of fasteners. Hayakawa et al (2004) found that cold forging die fracture was indicated by the decrease of AE fractal property.…”
Section: Introductionmentioning
confidence: 99%
“…AE generated during upset forging and diskforming operations of a C-Mn steel has been modeled, and it has been reported that the AE signals are characterized by a peak at low upset and reduced AE after 10% deformation [7]. A detection method of damage and fracture of forging tools during forming operation by using fractal property of AE signals has been proposed [11]. Pattern recognition analysis of AE signals has been used for enhancing the signal to noise ratio of the detected AE signals during an industrial deep drawing process [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, complexity of force/displacement signals and associated difficulties in interpretation of the signals and limitations of their use do not usually give desirable results [4]. In comparison to such force/displacement signals, the use of AE for on-line monitoring of forming processes is known to offer unique advantages [4][5][6][7][8][9][10][11][12]. In the earlier investigations [5][6][7], AE associated with forming processes has been attributed to generation of dislocations in the workpiece material.…”
Section: Introductionmentioning
confidence: 99%